Differential modulation of word recognition by semantic and spatial orienting of attention. - Cristescu, T; Nobre, A (2008)
In the present study, we investigated the ability to orient attention to abstract associative features of complex stimuli, more specifically, to the semantic categories of visual word stimuli. We compared the behavioral and electrophysiological effects of semantic orienting with those elicited by spatial orienting to word stimuli. Two parallel, cued lexical-decision tasks, with semantic- or spatial-orienting cues, were used. Results showed that both semantic and spatial orienting facilitated behavioral performance. The event-related potential analysis revealed different and non-overlapping patterns of modulation of word processing by semantic and spatial orienting. Modulation by semantic orienting started later, affecting only the potentials linked to conceptual or semantic processing (N300 and N400). The pattern of N300/N400 modulation in the semantic-orienting condition was similar to that observed in semantic-priming tasks, and was compatible with the operation of controlled semantic processes. Spatial orienting significantly enhanced the amplitude of the early visual potential P1 as well as the language-related N400 potential. These findings showed that the similar end-result of behavioral facilitation by semantic and spatial orienting is achieved through largely distinct mechanisms acting upon separate levels of stimulus analysis.